The criminal triad : psychosocial development of the criminal personality type - Harmening, William M. (Charles C Thomas Publisher, Ltd., 2010)
What is it that compels a person to choose a life of crime and deviancy over one of responsibility and social conformity? To understand exactly how and why that choice is ultimately made, we must turn to the discipline of psychology. The author presents and then deconstructs his own unique formulation of the internal deterrence system, and looks specifically at the psychosocial development of each of the proposed component partsattachment, morality, and identity. He then weaves together an example of the developing child and the role played by parents, peers, and internal psychological proces.